Governance and Internationalization of Indonesian Islamic Higher Education: A Comparative Study of UIII & UIN SGD Bandung - Qeysha, Anza Zahya (Sosiohumaniora, 2025)
Governance and internationalization are critical determinants in the transformation of Islamic higher education institutions into globally competitive entities. This study explores the governance frameworks and internationalization strategies of Universitas Islam Internasional Indonesia (UIII) and Universitas Islam Negeri Sunan Gunung Djati Bandung (UIN SGD Bandung), focusing on their alignment with Salmi's (2009) world-class university transformation model, which emphasizes talent concentration, abundant resources, and favorable governance. Through qualitative analysis of secondary data, including institutional annual reports (2021–2023) and semi-structured interviews with key stakeholders, this research identifies disparities in autonomy, resource mobilization, and internationalization initiatives stemming from differences in governance status—PTN-BH for UIII and PTN-BLU for UIN SGD Bandung. Findings reveal that UIII leverages its autonomy to enhance resource flexibility, establish global partnerships, and attract a diverse international student body, positioning itself as a global hub for Islamic scholarship. Conversely, UIN SGD Bandung focuses on regional engagement through outward mobility and dual-degree programs but faces challenges not only in financial independence but also in its limited prioritization in national-level internationalization policies. These factors constrain its ability to implement more impactful global initiatives and enhance postgraduate program quality. The study concludes that while UIII exemplifies third-generation cross-border education, UIN SGD Bandung remains within the first-generation model. Furthermore, criticism of governance and internationalization becomes an essential aspect of this research, considering the disparities between the two that mutually impact these aspects.